Extended Double Bond Conjugation in the Chalcone Framework Favours MAO-B Inhibition: A Structural Perspective on Molecular Dynamics - Agoni, Clement; Issahaku, Abdul R.; Abdelgawad, Mohamed A.; Khames, Ahmed; Soliman, Mahmoud E.S.; Mathew, Bijo (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: The monotropic membrane protein monoamine oxidase B (MAO-B) has been shown to be a crucial drug target for the treatment of neurodegenerative diseases. The design of recent inhibitor therapeutic agents of MAO-B involves conjugation and modification of a chalcone scaffold comprising two aryl or heteroaryl rings connected via a short spacer unit with rotatable bonds. Supported by experimental data, these modifications often result in high potent inhibitor compounds. Methods: In this study, we employ molecular dynamics simulations to unravel the impact of extended double bond conjugation in two novel compounds, F1 and MO10, toward the inhibition of the MAO-B protein. It was revealed that extended double bond conjugation induced a unidirectional orientation and motion of F1 and MO10, suggesting a stable binding pocket anchorage favouring high-affinity pocket interactions. Results: Conformational analyses also revealed that the incorporated double bond extension impeded the motion of individual binding pocket residues, which subsequently disrupted the functionality of MAO-B. Discussion: Real-time structural dynamics also revealed that the extended double bond conjugation mediated peculiar interactions with MAO-B binding pocket residues characterized by π-alkyl, π-π stacking, and π-sulphur interactions which buried both compounds into the hydrophobic core of MAO-B and ultimately induced higher binding affinities of both F1 and MO10. Conclusion: These insights present useful structural perspectives of the extended double bond conjugation associated with the experimentally reported enhanced inhibitory activity of F1 and MO10 against MAO-B.
Keywords: conformational analyses